A Co-intercalation enhanced V-based cathode material for fast charge aqueous zinc ion batteries. Issue 80 (16th September 2021) - Zhang, Shangshang; Liu, Zhenjiang; Li, Lun; Li, Shengkai; Zhang, Shuqi; Tang, Yudie; Yu, Jiale; Zhang, Haiyan
Abstract : H2 O–H–Na co-intercalation V-base material exhibited an excellent fast charging and Zn 2+ storage performance with the reversible phase transformed. Abstract : H2 O–H–Na co-intercalation is beneficial to enhance the structure of open framework V-based materials, leading to the improvement of Zn 2+ transport kinetics and solid-state solubility in V-based electrodes. Zn|Zn(CF3 SO3 )2 |HNaV6 O16 ·4H2 O exhibits an excellent specific capacity of 432.4 mA h g −1 and a long-term cyclic performance up to 800 cycles at 2.0 A g −1 with a reversible phase transformation. For the fast charge capability, a high specific capacity of 411.2 mA h g −1 is achieved with a coulomb efficiency of 100%. The co-intercalation structure can provide a new strategy for the design of fast charge cathode materials in aqueous zinc ion batteries (AZIBs).